Determination of Public Purchasing Power and Brand Image of Cooking Oil Scarcity and Price Increases of Essential Commodities - M. Ridho Mahaputra; Saputra, Farhan (International Journal of Advanced Multidisciplinary, 2022)
Cooking oil is one of the primary needs of the Indonesian people. The habits of the Indonesian people cannot be separated from the use of cooking oil in processing various types of dishes. This makes cooking oil a crucial role. As the largest Crude Palm Oil (CPO) producing country globally, it should not be a problem for Indonesia to meet its domestic cooking oil needs. In addition to meeting the needs of households and small industries, significant industries also require cooking oil as a component of producing one of the products. For this reason, it is necessary to have a strict policy taken by the government so that the scarcity of cooking oil and the increase in the price of essential commodities can be resolved quickly. This study aims to determine people's purchasing power, brand image, scarcity of cooking oil, and price increases of essential commodities.